The tough standard: the hard truths about masculinity and violence - Levant, Ronald F. (Oxford University Press, 2020)
"Ronald F. Levant, Ed.D., ABPP, is Professor Emeritus of Psychology, the University of Akron. Dr. Levant earned his bachelors in psychology from the University of California, Berkeley, and his doctorate in Clinical Psychology and Public Practice from Harvard University. He served on the faculty of Boston University for 13 years, where he directed the nationally prominent Fatherhood Project, an innovative community outreach program that offered preventive psychological services to men and their families. Following a brief stint at Rutgers University with a joint appointment in the Graduate Schools of Education and Applied and Professional Psychology, he served for seven years on the faculty of Harvard Medical School at The Cambridge Hospital, and then for eight years as Dean and Professor, Center for Psychological Studies, Nova Southeastern University. At the University of Akron, he served for four years as Dean of the College of Arts and Sciences, and nine years as Professor of Psychology. Dr. Levant has authored, co-authored, edited, or co-edited 19 books and 250 peer-refereed journal articles and book chapters in family and gender psychology and in advancing professional practice"--